PENINGKATAN KEBERSIHAN MULUT MELALUI EDUKASI BERBASIS TOT BAGI GURU DAN ORANG TUA DALAM KEMITRAAN SEKOLAH - Sarianoferni Sarianoferni; Noengki Prameswari; Yongki Hadinata; Henu Sumekar; Ayulistya Paramita; Cane Lukisari; Yoifah Rizka Wedarti; Nafiah Nafiah; Twi Agnita Cevanti; Agni Febrina Pargaputri; Dianty Saptaswari; Meinar Nur Ashrin; Ghita Hadi Hollanda; Aprilia Aprilia; Dwi Setyaningtyas (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Dental caries in children remains a significant public health problem in Indonesia, particularly among primary school-aged children. Limited oral health literacy and insufficient involvement of teachers and parents in oral hygiene guidance contribute to the high prevalence of dental caries. This study aimed to enhance children’s oral hygiene knowledge and practices through Training of Trainers (ToT)-based education for teachers and parents within a partnership between the Faculty of Dentistry, Hang Tuah University, and El Rahma Islamic Boarding School, Surabaya. A pretest–posttest design was applied, involving fifth-grade students as research subjects. Teachers and parents received ToT-based training delivered by dental professionals and subsequently provided oral health education to students. Knowledge levels were assessed using questionnaires administered before and after the intervention and analyzed using the Wilcoxon Signed-Rank Test. The results demonstrated a significant increase in students’ mean knowledge scores, from 58.14 ± 21.30 at pretest to 77.21 ± 18.30 at posttest (p < 0.05). In addition, partner satisfaction questionnaires indicated a very high level of satisfaction with the program implementation. In conclusion, ToT-based oral health education involving teachers and parents is effective in improving children’s oral hygiene knowledge and has the potential to promote sustainable oral health behavior changes within the school environment.